Anemonin improves intestinal barrier restoration and influences TGF-β1 and EGFR signaling pathways in LPS-challenged piglets. Issue 5 (July 2016) - Xiao, Kan; Cao, Shu Ting; Jiao, Le Fei; Lin, Fang Hui; Wang, Li; Hu, Cai Hong
The present study was aimed at investigating whether dietary anemonin could alleviate LPS-induced intestinal injury and improve intestinal barrier restoration in a piglet model. Eighteen 35-d-old pigs were randomly assigned to three treatment groups (control, LPS and LPS+anemonin). The control and LPS groups were fed a basal diet, and the LPS + anemonin group received the basal diet + 100 mg anemonin/kg diet. After 21 d of feeding, the LPS- and anemonin-treated piglets received i.p. administration of LPS; the control group received saline. At 4 h post-injection, jejunum samples were collected. The results showed that supplemental anemonin increased villus height and transepithelial electrical resistance, and decreased crypt depth and paracellular flux of dextran (4 kDa) compared with the LPS group. Moreover, anemonin increased tight junction claudin-1, occludin and ZO-1 expression in the jejunal mucosa, compared with LPS group. Anemonin also decreased TNF-α, IL-6, IL-8 and IL-1β mRNA expression. Supplementation with anemonin also increased TGF-β1 mRNA and protein expression, Smad4 and Smad7 mRNA expressions, and epidermal growth factor and epidermal growth factor receptor (EGFR) mRNA expression in the jejunal mucosa. These findings suggest that dietary anemonin attenuates LPS-induced intestinal injury by improving mucosa restoration, alleviating intestinal inflammation and influencing TGF-β1 canonical Smads and EGFR signaling pathways.